Responses of Soil Microbial Biomass and Enzyme Activities to Natural Restoration of Reclaimed Temperate Marshes After Abandonment - Wang, Chunguang; Li, Haixing; Sun, Xiaoxin; Cai, Tijiu (Frontiers in Environmental Science, 2021)
Restoration of reclaimed marshes has great effects on soil biological processes. However, the responses of soil microbial properties (microbial biomass and enzyme activities) to natural restoration of reclaimed marshes is poorly studied, especially in a long restoration chronosequence. This study assessed the responses of soil microbial properties to natural restoration and investigated the relationships between soil microbial properties and soil physico-chemical and plant properties. We selected a restoration chronosequence (1, 4, 8, 13, 17, 27 years) after farmland abandonment, a soybean field, and a natural marsh in Sanjiang Plain, northeast China. For each site, we analyzed the soil microbial biomass carbon and nitrogen (MBC and MBN), four enzymes (β-glucosidase, invertase, catalase, urease) activities, soil physico-chemical properties at 0–50 cm depths, and plant properties (biomass, height, and coverage). The MBC and MBN contents increased with restoration time, but MBN content slowed down after 8 years of restoration. After 27 years of restoration, the soil MBC and MBN contents were 15.7 and 3.2 times of those in the soybean field, but the largest contents of MBC and MBN in the restored sites were 7.78%, 27.76% lower than those in natural marshes, respectively. Moreover, soil enzyme activities and the geometric mean of enzymatic activities (GME) also increased with restoration but slowed down after 13 years of restoration. After 27 years of restoration, the GME was 2.9 times than that in the soybean field, but the largest GME in the restored sites was 31.15% lower than that in the natural marsh. MBC and MBN contents, soil enzyme activities, and GME had significant relationships with soil C:N ratio, organic carbon, nutrients (total nitrogen, available nitrogen, total phosphorus), bulk density, moisture content, pH, plant properties (i.e. biomass, height, and coverage) (P < 0.01). Redundancy analysis revealed that soil C:N ratio, pH, moisture content, total nitrogen and phosphorus were main factors affecting MBC and MBN contents and enzyme activities. In conclusion, soil microbial properties can respond positively to the natural restoration process of the reclaimed marshes and were significantly correlated with specific parameters of soil physico-chemical and plant properties.